PERJANJIAN LISENSI SEBAGAI BENTUK PENGALIHAN HAK KEKAYAAN INTELEKTUAL - Dani Amran Hakim (Yurisprudentia: Jurnal Hukum Ekonomi, 2021)
There are numerous sophisticated innovations emerge in this modern era. This leads to copyright works in the form of intellectual property rights (HKI). Intellectual property right protects the owner’s right of the property. Other parties may use the property to gain benefit only if the owner granted the license.  Based on the analysis of the discussion, license is a transfer of intellectual property rights as stated in the form of an agreement. The parties involved in the agreement are the licensor and the licensee. License is a form of right to take one or a series of actions, granted by those who have rights in the form of a license as stipulated in the agreement.  According to Law number 28 of 2014 concerning copyright, a license is a permit given by a copyright holder to other parties to announce and / or reproduce their work or related rights products with certain conditions.  In the form of a license transfer, the inventor of the property still has certain economic rights from his/her work which are transferred to the holder of intellectual property rights.